Analysis of NEC cases registered in the human milk bank database - Mizuno, Katsumi; Wada, Yuka S.; Sakurai, Motoichiro; Tani, Yuki; Miyata, Masafumi; Shindo, Jun; Nishimaki, Shigeru; Den, Hiroki (Frontiers in Pediatrics, 2025)
BackgroundNecrotizing enterocolitis (NEC) remains a major cause of morbidity and mortality in extremely low birth weight infants (ELBWIs), despite widespread donor human milk (DHM) use. This study examined NEC cases among DHM recipients to explore potential contributing factors.MethodsWe retrospectively analyzed 1,425 infants registered in Japan's human milk bank database (2018–2023). NEC cases at Bell stage ≥ II were confirmed by attending physicians. Infants who received DHM only after NEC onset were excluded. Cases were categorized by onset timing and associated clinical factors.ResultsAmong 1,324 very low birth weight infants, 21 (1.58%) developed NEC, with 20 requiring surgical intervention. Median gestational age and birth weight were 25.1 weeks and 637 g, respectively. NEC onset was classified as follows: within 7 days of birth (n = 5), after 2 months (n = 5), after formula or fortifier use (n = 6), associated with hemodynamic changes (n = 7), or of unknown etiology (n = 4). Common factors included symptomatic PDA, congenital heart disease, infection, formula exposure, and ophthalmologic procedures.ConclusionNEC can develop despite DHM use, often in association with early infections, PDA, or fortification. Strategies to further reduce NEC incidence should include management of hemodynamic instability, delayed formula introduction, and use of exclusive human milk-based diets. Further research should explore potential roles of ophthalmologic interventions and human milk fortifiers in NEC development.